The allocation of attention in change detection and change blindness - Schankin, Andrea; Schubert, Anna-Lena; Hagemann, Dirk (Journal of psychophysiology, 2017)
Visual change detection often fails when observers’ attention is distracted by some other visual disruptions in the environment that occur simultaneously with the change. This phenomenon is called change blindness. It has been claimed that selective attention is necessary for successful change detection. In the current experiment, two mechanisms of attention allocation in such a task were investigated. First, the number of distracting stimuli was varied to distract observers’ attention and, second, possible change positions were highlighted to allow observers to better focus on potential change locations. The N2pc component of the event-related potential was measured as an indicator of attentional selection. The results show that the sensitivity for changes increased either when observers were less distracted or when they were able to better focus their attention. However, these two mechanisms were reflected differently by the N2pc component. When observers’ attention was less distracted by a lower number of mudsplashes, the N2pc component occurred earlier. In contrast, when observers were able to better focus their attention on potential change locations, the N2pc component not only occurred earlier but also showed an additional enhancement in amplitude. That is, successful change detection depends on both, the properties of distracting and of changing objects. They determine the speed and intensity of the allocation of attention toward a change. (PsycINFO Database Record (c) 2016 APA, all rights reserved)